2001
DOI: 10.1111/1468-0335.00234
|View full text |Cite
|
Sign up to set email alerts
|

Non‐transitive Choice: Event‐Splitting Effects or Framing Effects?

Abstract: Recent studies have examined possible causes of the robust empirical failure of the transitivity axiom of expected utility theory by pitting regret aversion against alternative explanations such as event-splitting effects. These tests show that cycles replicate when the latter are controlled, but are sensitive to changes in problem representation. The control for eventsplitting effects, however, does not rule out their contribution to cyclical choices in some circumstances. An experiment is reported which inve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
37
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(37 citation statements)
references
References 12 publications
0
37
0
Order By: Relevance
“…Another possible explanation is that PR arises as a consequence of context-free, but nontransitive preferences. Persistent non-transitive cycles of choice analogous to PR have been observed in experimental studies Sugden 1989, 1991;Humphrey 2001), but the only preference theory that has been put forward to explain such behaviour is regret theory (Bell 1982;Loomes and Sugden 1983), which has failed other tests (Starmer and Sugden 1998). A third approach is to explain PR by supplementing a conventional theory of preferences with some mechanism of stochastic error; but this has been shown to be empirically unconvincing (Schmidt and Hey 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Another possible explanation is that PR arises as a consequence of context-free, but nontransitive preferences. Persistent non-transitive cycles of choice analogous to PR have been observed in experimental studies Sugden 1989, 1991;Humphrey 2001), but the only preference theory that has been put forward to explain such behaviour is regret theory (Bell 1982;Loomes and Sugden 1983), which has failed other tests (Starmer and Sugden 1998). A third approach is to explain PR by supplementing a conventional theory of preferences with some mechanism of stochastic error; but this has been shown to be empirically unconvincing (Schmidt and Hey 2004).…”
Section: Discussionmentioning
confidence: 99%
“…In this literature, investigators analyze frequencies of response patterns, which is a better way to present the data. Studies found that violations of transitivity predicted by regret theory are more frequent than violations of the opposite pattern (Humphrey, 2001;Loomes, Starmer, & Sugden, 1989, 1991Loomes & Taylor, 1992;Starmer & Sugden, 1998). Starmer (1999) also used this criterion of asymmetry to argue for another type of intransitivity.…”
mentioning
confidence: 99%
“…A number of previous studies attempted to test transitivity Loomes et al 1989Loomes et al , 1991Loomes and Taylor 1992;Humphrey 2001;Starmer 1999;Starmer and Sugden 1998;Tversky 1969). However, these studies remain controversial; there is not yet consensus that there are situations that produce substantial violations of transitivity (Luce 2000;Iverson and Falmagne 1985;Iverson et al 2006;Regenwetter andStober 2006, Sopher andGigliotti 1993;Stevenson et al 1991).…”
mentioning
confidence: 99%
“…] A problem in previous empirical tests of regret theory is that certain confounds were present in those studies (Humphrey 2001;Starmer and Sugden 1998). Probably the most important problem was that different forms of the gambles were used in different choices.…”
mentioning
confidence: 99%
See 1 more Smart Citation